Analisis Pajak Penghasilan Badan Dalam Rangka Menghindar Sanksi Pajak dan Akuntansi Perpajakannya Pada CV PO Karya Baru - Pangerapan, Gianluigi; Elim, Inggriani; Suwetja, I Gede (Universitas Sam Ratulangi, 2024)
Tax Revenue is the biggest source of state revenue. For that the recording and calculation of taxable income must be done correctly, and report must be done on time. The purpose of this study is to determine whether the company has calculated, recorded corporated tax correctly, and also the tax calculation has avoided tax penalties. This research was conducted at CV PO Karya Baru. Data analysis method used is descriptive qualitative method. The result of the study found that the company had not recorded Article 25 Income Tax correctly and the company had paid attention to the fiscal correction in calculating the Article 25 Income owed but had not calculated the correctly and if an inspection is conducted the company could be penaltized because it has passed the due date. In conclusion the company must be careful in keeping journal for the recording of Article 25 Income Tax and pay attention to the overall fiscal correction in the context of determining the Article 25 Income Owed and the company must settle tax penalties if an inspection is carried out.